新汉语水平考试（HSK 3.0）的设计原则及其对外汉语教学启示 - Sukma Tajuddin; Sukma Sukma; Leni Cahyati (Sinolingua: Journal of Chinese Studies, 2026)
The reform of the Chinese Proficiency Test under the New HSK 3.0 framework marks a significant shift in the assessment of Chinese as a Foreign Language (CFL). While previous studies primarily examine vocabulary expansion or standard alignment, the design principles underlying the reform remain underexplored. This study investigates the conceptual logic of the New HSK 3.0 examination system and its implications for CFL education. Using qualitative document analysis and multi-source literature review, the research analyzes key policy documents, including the Chinese Proficiency Grading Standards for International Chinese Language Education (CEFCIL) and the HSK Examination Syllabus (2025). The findings identify three core design principles: multidimensional competence construction, communicative authenticity, and receptive-productive differentiation in character learning. These principles are reflected in the expansion to a nine-level proficiency framework and the redistribution of vocabulary and character requirements across learning stages. The study provides insights into Chinese language assessment reform and its implications for curriculum design and language teaching in international Chinese education.